Penerapan Metode Stimulasi Multimodal Pada Gangguan Bahasa Ekspresif Pasien dengan Afasia Broca: Laporan Kasus - Sa`diah, Hikmatun; Hanifa, Putri (Akademi Terapi Wicara, 2023)
The general objective of the study is to optimize the recovery of post-stroke clients so that they are able to perform quality functional communication independently.